Evaluation of bonding strength of some tropical wood species as a function of surface roughness - Tan, Hui Ling. (2012)
For many countries, wood is widely used as a raw material in the furniture industry. Some of the commonly available tropical wood species in Singapore were evaluated. Experiments were conducted for Kapur, Meranti and Pine wood to find out the adhesion bonding strength as a function of surface roughness. The wood pieces were sanded with sandpaper of grit size 80, 100 and 240. Surface roughness of the wood pieces was recorded using Mitutoyo Surftest SJ301. Thereafter, the wood pieces were glued and the adhesion bonding strength was tested with Instron Universal Tester 5569. Density of wood was also determined.